PERAN SERTIFIKASI HALAL TERHADAP PENGEMBANGAN USAHA UMKM SEBLAK PRASMANAN ELSEVAA DI SIDOARJO - Nur Halizah, Siti; Rohman, Abdur (LPPM STAI DARUSSALAM LAMPUNG, 2025)
This study aims to evaluate the strategic role of halal certification in the development of MSME culinary businesses, with a case study on Seblak Prasmanan Elshevaa in Sidoarjo. Halal certification not only guarantees the halalness of products for Muslim consumers, but is also an important instrument in improving business competitiveness, expanding market reach, and building consumer confidence. Through a qualitative approach with a case study method, data was collected through in-depth interviews and document analysis. The findings show that halal certification has a significant impact on customer growth and strengthening Elshevaa's brand image. This confirms the crucial role of halal certification in strengthening consumer trust and increasing competitiveness in the sharia-based culinary industry.